2013
DOI: 10.7589/2012-08-215
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Antibodies to Spotted Fever Group Rickettsia spp. and Ehrlichia spp. in Coyotes (Canis latrans) in Oklahoma and Texas, USA

Abstract: ABSTRACT:Coyotes (Canis latrans) are commonly infested with ticks, including Amblyomma americanum, the predominant vector of Ehrlichia chaffeensis and Ehrlichia ewingii; Dermacentor variabilis, an important vector of Rickettsia rickettsii; and Amblyomma maculatum, a major vector of Rickettsia parkeri, a spotted fever group (SFG) Rickettsia. To determine the degree to which coyotes are infected with or exposed to tick-borne bacterial disease agents, serum samples collected from coyotes in Oklahoma and Texas wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…The Ehrlichia rrs detected in one A. sculptum adult and nymph, one A. parvum and one Amblyomma larvae pool were closely related to E. canis ( 12 ). In the USA, specific antibodies to E. canis were detected in 18% (9/50) coyotes sampled in Texas and Oklahoma, USA, using a p16 peptide-based microtiter plate ELISA ( 79 ).…”
Section: Molecular Prevalence and Diversity Of Tick-borne Anaplasmatamentioning
confidence: 99%
“…The Ehrlichia rrs detected in one A. sculptum adult and nymph, one A. parvum and one Amblyomma larvae pool were closely related to E. canis ( 12 ). In the USA, specific antibodies to E. canis were detected in 18% (9/50) coyotes sampled in Texas and Oklahoma, USA, using a p16 peptide-based microtiter plate ELISA ( 79 ).…”
Section: Molecular Prevalence and Diversity Of Tick-borne Anaplasmatamentioning
confidence: 99%
“…“R. amblyommii” can stimulate an immune response in both canids [39, 43, 44], but there is no evidence to support the pathogenicity of C . “R.…”
Section: Discussionmentioning
confidence: 99%
“…Establishing baseline distribution maps and updating historical maps are critical to understanding how tick populations are spread over diverse eco‐zones as well as evaluating changes in the potential risk for specific tick‐borne diseases in a specific geographic area. Given the dramatic increase of tick‐borne diseases in human and animal populations in Oklahoma over the last 15 years (Openshaw et al , Dahlgren et al , Starkey et al , Little et al , Carmichael et al ), it is critical to understand where the tick species that are responsible for transmitting specific pathogens are distributed. By using active surveillance, the current study added an additional 18 counties of reported and established populations to the list compiled from published studies for distribution of D. variabilis.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of tick‐borne disease continues to increase in humans and companion animals in the United States (CDC ). One area of concern is the south‐central region of the U.S. that has seen an increase in ehrlichiosis, Rocky Mountain spotted fever, and tularemia among human populations, and ehrlichiosis and hepatozoonosis among veterinary species (Openshaw et al , Dahlgren et al , Starkey et al , Carmichael et al , Little et al ). While it is apparent that the incidence of these diseases is increasing, the distribution maps for principal tick vectors in this region are not available, are outdated, or are based on passive collections (Dennis et al , Cortinas and Spomer , James et al , Eisen et al ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation